2021
DOI: 10.1038/s41398-021-01423-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased GFAP concentrations in the cerebrospinal fluid of patients with unipolar depression

Abstract: Inflammatory processes involving altered microglial activity may play a relevant role in the pathophysiology of depressive disorders. Glial fibrillary acidic protein (GFAP) and calcium-binding protein S100B are considered microglial markers. To date, their role has been studied in the serum and tissue material of patients with unipolar depression but not in the cerebrospinal fluid (CSF). Therefore, the aim of the current study was to examine GFAP and S100B levels in the CSF of patients with major depression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 71 publications
(77 reference statements)
1
20
0
Order By: Relevance
“…Plasma GFAP levels are also elevated in individuals with neuropsychiatric illnesses who lack brain radiological abnormalities (Esnafoglu et al, 2017). Decreased GFAP expression has been observed in post-mortem cerebral tissues from patients with MDD (Michel et al, 2021; Rajkowska et al, 2018) and the expression of both GFAP mRNA and protein is decreased in astrocytes in the postmortem locus coeruleus of individuals with MDD (Chandley et al, 2013). GFAP mRNA is also decreased in the postmortem prefrontal cortex of depressed suicide victims (Nagy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma GFAP levels are also elevated in individuals with neuropsychiatric illnesses who lack brain radiological abnormalities (Esnafoglu et al, 2017). Decreased GFAP expression has been observed in post-mortem cerebral tissues from patients with MDD (Michel et al, 2021; Rajkowska et al, 2018) and the expression of both GFAP mRNA and protein is decreased in astrocytes in the postmortem locus coeruleus of individuals with MDD (Chandley et al, 2013). GFAP mRNA is also decreased in the postmortem prefrontal cortex of depressed suicide victims (Nagy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to elevated levels of vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF), stimulated peripheral whole blood from individuals with MDD was shown to have an increased PDGF production (Rachayon et al, 2022). Patients with MDD have elevated CSF GFAP levels (Michel et al, 2021) and serum GFAP levels that may rise with increasing MDD severity (Steinacker et al, 2021). Plasma GFAP levels are also elevated in individuals with neuropsychiatric illnesses who lack brain radiological abnormalities (Esnafoglu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent preclinical study reported that 6 weeks of CUS followed by another 6 weeks of social isolation induced an increase in the number of GFAP + cells in the DG (Du Preez et al, 2021). Moreover, Michel et al (2021) found that the level of GFAP was significantly higher in patients with unipolar depression than in mentally healthy controls with idiopathic intracranial hypertension. Hence, both the loss and increase of astrocytes may be responsible for stressinduced depressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria for the control group were as follows: secondary forms of intracranial hypertension and psychiatric or other neurological disorders (except headaches). The control group was already published in earlier articles [ 27 , 31 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%